Strategi dalam Menciptakan dan Meningkatkan Kehidupan Religius di Sekolah: Tantangan dan Solusi (International Forum of Researchers and Lecturers, 2025)
This study discusses strategies for creating and enhancing religious life in schools as a means of shaping students’ moral character in the face of globalization. Despite the implementation of various religious programs, challenges such as low student participation, lack of teacher role models, and negative social and technological influences persist. The aim of this study is to formulate comprehensive and adaptive strategies to foster a religious atmosphere in schools. The research employs a qualitative method with a library research approach through content analysis of educational and religious literature. The findings indicate that religious life in schools can be strengthened through the integration of religious values into the curriculum, the development of a religious school culture, reinforcement of religious extracurricular activities, active roles of Islamic Religious Education (PAI) teachers, involvement of parents and communities, wise use of technology, and ongoing evaluation. This study offers practical and applicable strategies to build a school environment that supports students’ holistic spiritual development.